Mimics and chameleons in motor neurone disease. - Turner, M; Talbot, K (2013)
The progression of motor neurone disease (MND) is currently irreversible, and the grave implications of diagnosis naturally fuels concern among neurologists over missing a potential mimic disorder. There is no diagnostic test for MND but in reality there are few plausible mimics in routine clinical practice. In the presence of a progressive pure motor disorder, signs such as florid fasciculations, bilateral tongue wasting, the 'split hand', head drop, emotionality, and cognitive or behavioural impairment carry high positive predictive value. MND is clinically heterogeneous, however, with some important chameleon-like presentations and considerable variation in clinical course. Lack of confidence about the scope of such variation, or an approach to diagnosis emphasising investigations over clinical common sense, has the potential to exacerbate diagnostic delay in MND and impede timely planning of the care which is essential to maximising quality of life.